Лікарські рослини Українських Карпат - Скибіцька, М. (Праці наукового товариства ім. Шевченка, 2003)
Повідомлено про історію дослідження лікарських рослин Українських
Карпат, їхнє значення в офіцинальній і народній медицині. Виділено
групи лікарських рослин за вмістом біологічно активних речовин (БАР).
Наведено приклади рідкісних видів лікарських рослин і обґрунтовано
потребу їх охорони. There is an information about the history of the research of the Ukrainian Carpathian
medical plants, of their importance for the official and folk medicine. The groups of medical
plants after the contains of prevalent groups of biological active substances were singled out .
Standards of rare species of medical plants and the necessity to protect them are given there.